Per causa de certs crims per aquells perpetrats e comeses. Notícies, sancions i càstigs dels perseguits per la justícia valenciana al segle XV. - BARBER BLASCO, ALBERTO (Scripta, 2020)
Which cotidian conflicts were origined in the XVth century in Valencia? Who were the criminals that acted outside the law and break the convivence? How they were punished? These are some cuestiones that we want to respond with our propose. Our objetive will be to show the news, fines and punishments that testify fights, sorcery, path's raiders and other criminal practices were produced in the Valencia's geographic sorroundings, even outside of the Valencia's kingdom borders. Our reserach will be di dit showing different sources registers as the account books of the city and the account and diligences books of the Criminal Justice. Thanks to these sources we will be able to make known some of the Characters who were the protagonists of these misdeeds and their lifestyle.